A Tourism Introduction Application Using Augmented Reality - Leni Fitriani; Dini Destiani; Hasbi Muhtadillah (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2022)
Tourism is a journey from one place to another. Whether it is an individual, a group, or a company, participants on this trip are interested in mental balance, such as reducing stress, entertaining themselves, and refreshing. A tourist attraction is one of the products or advantages of an area, where the region can create income and attract tourists to their tourist destinations. One way to promote tourism more attractively is with augmented reality media. This tourism introduction application using Augmented reality technology aims to make it easier for tourists to get to know tourism with interactive media. This tourism introduction application is needed for promotional media, including video playback features of Augmented reality technology and information about tourism. Augmented Reality is a real object in an area map that will become a marker object by detailing the tourist plan. A scan can be carried out to display 2D images, text, audio, and video with the android platform so that it can make it easier for users to use it. This research aims to design and build a tourism introduction application with the Application of Augmented Reality Technology. This research uses the Multimedia Development Life cycle method, with six stages: concept, design, material collecting, assembly, testing, and distribution, with the testing method using alpha and beta tests. The results of this research are in the form of an Android-based tourism introduction augmented reality application. This application can give contributions to assist tourists in finding information about tourism in an area and help the Department of Tourism and Culture promote tourism in the region more attractively.